Ask a New Question
Search
y= tan(2tan^-1x/2), show that dy/dx= 4(1+y^2)/4+x^2
Genral solution of:
2tan x + 3=0 Solve for x if: 2tan x +3 =0 and x E[-180;180]
1 answer
asked by
Thule
626 views
y= tan(2tan^-1x/2), show that dy/dx= 4(1+y^2)/4+x^2
2 answers
asked by
saadia
486 views
Show that the following are not trigonometric identities
1.tan 2x = 2tan x 2. sec x= sqr rt 1+tan^2 x 3. sin(x+y)=sin x +sin y
1 answer
asked by
Liv
877 views
Which of the following functions of x can be integrated with respect to x without integration by parts, and purely using
3 answers
asked by
Alice
2,259 views
Q.NO.1: Show that the function z=ln(x^2 + y^2)+2tan^-1(y/x) satisfies Laplace’s equation.
(∂^2z/∂x^2)+(∂^2z/∂y^2)=0
0 answers
asked by
akash
517 views
Q.N0.2: Show that u(x,y)=ln(x^2 + y^2) and v(x,y)=2tan^-1(y/x) satisfy Cauchy-Riemann equations
(∂u/∂x)=(∂v/∂y) and
1 answer
asked by
akash
428 views
Q.NO.1: Show that the function z=ln(x^2 + y^2)+2tan^-1(y/x) satisfies Laplace’s equation.
(∂^2z/∂x^2)+(∂^2z/∂y^2)=0
1 answer
asked by
akash
1,154 views
cot^-1(2tan(cos^-18/17))+tan^-1(2tan(sin^-18/17))=tan^-1300/161
1 answer
asked by
hasee
786 views
i)The angle á lies between 0 and 90 and is such that 2tan sqaure á + sec square á=5-4tan á. show that
3tan square á
1 answer
asked by
Amr
1,060 views
sec^2xcotx-cotx=tanx
(1/cos)^2 times (1/tan)-(1/tan)=tan (1/cos^2) times (-2/tan)=tan (-2/cos^2tan)times tan=tan(tan) sq. root of
2 answers
asked by
Trig
857 views